Pengaruh Media Ular Tangga Terhadap Hasil Belajar Siswa Di Kelas 1 Phatnawitya School Thailand - Meli Dwi Saputri; Veryliana Purnamasari; Ervina Eka Subekti (Journal on Education, 2025)
Because it can make the material easier to understand, the use of teaching media in learning activities is very important. The purpose of the following study is to clearly determine how the effect of snakes and ladders media is related to the learning outcomes of grade 1 students at Phatnawitya School Thailand. The research technique used is a quantitative approach using an experimental design with a total of 30 grade 1 students at Phatnawitya School Thailand odd semester of the 2023/2024 school year, using a pretest and posttest research design. Data collection techniques were recording, observation and testing. 10 multiple-choice questions were part of the written test used in this study instrument. The results of the assessment were obtained from the estimation results through the Paired Sample t-tests and the t-test results were obtained at a t value of -9.711. With a sig value (Two-Sided) of 0.000 and a significance level of 0.05. Signaling that the significance of 0.000 <0.05. So it can be stated that there is an impact of snakes and ladders media on the educational attainment of grade 1 students of Phatnawitya School Thailand.